Bonus–Malus systems with Weibull distributed claim severities. (19th May 2014) - Ni, Weihong; Constantinescu, Corina; Pantelous, Athanasios A.
Abstract One of the pricing strategies for Bonus–Malus (BM) systems relies on the decomposition of the claims' randomness into one part accounting for claims' frequency and the other part for claims' severity. By mixing an exponential with a Lévy distribution, we focus on modelling the claim severity component as a Weibull distribution. For a Negative Binomial number of claims, we employ the Bayesian approach to derive the BM premiums for Weibull severities. We then conclude by comparing our explicit formulas and numerical results with those for Pareto severities that were introduced by Frangos & Vrontos.